Peran Majlis Ta'lim dalam Pembentukan Identitas Keagamaan Remaja Pedesaan di Era Digital - Akfi Yusria Rizqi (Getpress Management Journals, 2025)
The digital era presents new challenges for teenagers in shaping their religious identity, especially due to the influence of social media such as TikTok. This study aims to examine the role of majlis ta'lim as a non-formal educational institution in shaping the religious identity of teenagers amid the digitalization trend. The study employs a qualitative approach using in-depth interviews with teenage participants of majlis ta'lim and the institution's administrators. The findings reveal that majlis ta'lim serves as an effective social space for instilling religious values in a moderate and contextual manner, as well as acting as a moral filter for teenagers in navigating the negative influences of social media. Additionally, majlis ta'lim has begun to adapt to digital technology by utilizing social media as a means of religious outreach and communication. The study emphasizes that while adolescents cannot completely escape digital influences, majlis ta'lim provides a strong foundation of values and moral control, ensuring that their religious identity remains positively and moderately preserved. These findings contribute to the development of religious education strategies relevant to the needs of today's teenagers and serve as a reference for religious education center administrators and policymakers in addressing the dynamics of globalization and modernization.